Various for 9 (Global Journal of Science Frontier Research, 2017)
number n=3529411764705882 by 2, then the result m=2n=7058823529411764 will contain the same digits. Moreover, we can cut n into two section n=bd with b=3529411764 and d=705882 such that m contains the same sections in reverse order: m=db.